Thyroid Hormone and Seasonal Rhythmicity - Dardente, Hugues; Hazlerigg, David G.; Ebling, Francis J. (Frontiers in Endocrinology, 2014)
Living organisms show seasonality in a wide array of functions such as reproduction, fattening, hibernation and migration. At temperate latitudes, changes in photoperiod maintain the alignment of annual rhythms with predictable changes in the environment. The appropriate physiological response to changing photoperiod in mammals requires retinal detection of light and pineal secretion of melatonin, but extraretinal detection of light occurs in birds. A common mechanism across all vertebrates is that these photoperiod-regulated systems alter hypothalamic thyroid hormone conversion. Here we review the evidence that a circadian clock within the pars tuberalis of the adenohypophysis links photoperiod decoding to local changes of thyroid hormone signalling within the medio-basal hypothalamus through a conserved thyrotropin/deiodinase axis. We also focus on recent findings which indicate that, beyond the photoperiodic control of its conversion, thyroid hormone might also be involved in longer term timing processes of seasonal programs. Finally, we examine the potential implication of kisspeptin and RFRP3, two RF-amide peptides expressed within the medio-basal hypothalamus, in seasonal rhythmicity.